The Effect of Giving a Combination of Cucumber and Tomato Juice on Overweight Female Blood Pressure (Menopouse) - Rahma Kusuma Dewi; Lindha Sri Kusumawati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Factors causing the occurrence of hypertension for women (menopause) are two types, factor that can not be changed and factor that can be changed, but the most dominant factor is the changable one (overweight/obesity). The occurrence of hypertension in some region could be an indicator of the welfareness level in that area. The purpose of this research was to determine the effect of cucumber and tomato juice combination on overweight women’s blood pressure (menopause). The research design used is pre-experimental research. The population studied were all of overweight women (menopause) in Kantil Posyandu/IHC counted 18 people, and sample obtained with the accidental sampling technique was 13 people. The research instrument used was the observation sheet. The results of this research were analyzed with wilxocon signed rank. The results of this research showed that the majority of overweight women (menopause) with hypertension before the giving of cucumber and tomato juice combination were experiencing the stage 1 hypertension, and after the giving of cucumber and tomato juice combination, majority of respondents had a normal blood pressure and mostly were experiencing pre hypertension. The analysis showed the existence of effects from the combination of cucumber and tomato juice on overweight women’s blood pressure (menopause). Based on the results, expected from the field researchers to improve the education and counseling program on both the suffering hypertension or not.